Performance Evaluation and Pounding Effects between KPFT Building Alternative Design for SGLC Building - Rusgiyanto Rusgiyanto (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2019)
Main Office building of the Faculty of Engineering (KPFT) is one of the buildings located within the complex of the Faculty of Engineering, Universitas Gadjah Mada. There is a plan to build a new building adjacent to the KPFT building. The design can interact simultaneously in support of earthquake so that the pounding effect can occur. The pounding effect due to earthquake loads is to improve the quality of KPFT building. This study applies numerical study to determine the effect of adding new structures around the old structure. This research uses 3 structure models, i.e. KPFT building without a wall (SKTD), the new Smart and Green Learning Center (SGLC) structure (SB), and the composite building (SG). This research uses linear time history analysis. There are 3 earthquake records including Superstition Hills-02, Darfield New Zealand, and El Mayor-Cucapah. The results shows story drift from the KPFT building (SKTD model) is reduced after the adjacent building has occurred. The performance level for SKTD models is Life Safety (LS), whereas the performance level for KPFT building after combining with the new structure is Operational (OP). The KPFT building after combining with new structure has a better performance level due to its drift ratio.